2012
DOI: 10.1128/cvi.05559-11
|View full text |Cite
|
Sign up to set email alerts
|

Humoral and Cellular Immune Responses to Yersinia pestis Infection in Long-Term Recovered Plague Patients

Abstract: Plague is one of the most dangerous diseases and is caused by Yersinia pestis. Effective vaccine development requires understanding of immune protective mechanisms against the bacterium in humans. In this study, the humoral and memory cellular immune responses in plague patients (n ‫؍‬ 65) recovered from Y. pestis infection during the past 16 years were investigated using a protein microarray and an enzyme-linked immunosorbent spot assay (ELISpot). The seroprevalence to the F1 antigen in all recovered patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 30 publications
1
30
0
3
Order By: Relevance
“…Mice vaccinated with Y. pestis KIM5 (lacking pgm) generated the CD4 and CD8 T cells that synergistically conferred protection against plague, but T cells from those vaccinated mice could not recognize LcrV (47). Patients who had recovered from plague also barely produced memory T-cell responses to LcrV antigens (58). Pettersson et al analyzed the localization of LcrV during infection of HeLa cells and were unable to detect any LcrV in the cytosol of the cells (59), but Nilles et al showed that small amounts of LcrV entered HeLa cells and suggested that this translocation appears to not result from injection via the T3SS (60).…”
mentioning
confidence: 99%
“…Mice vaccinated with Y. pestis KIM5 (lacking pgm) generated the CD4 and CD8 T cells that synergistically conferred protection against plague, but T cells from those vaccinated mice could not recognize LcrV (47). Patients who had recovered from plague also barely produced memory T-cell responses to LcrV antigens (58). Pettersson et al analyzed the localization of LcrV during infection of HeLa cells and were unable to detect any LcrV in the cytosol of the cells (59), but Nilles et al showed that small amounts of LcrV entered HeLa cells and suggested that this translocation appears to not result from injection via the T3SS (60).…”
mentioning
confidence: 99%
“…Nevertheless, a single dose of the EV NIIEG live vaccine conferred a prompt (day 7 post-vaccination) and pronounced immunity in vaccinees lasting for 10–12 months against bubonic and, to some extent, pneumonic plague [14, 85]. Yang’s group also posed hypothesis that the lack of the pgm locus might affect survival ability of EV76 in humans efficiently, limit its replication and dissemination and result in insufficient contact with immune cells [86], which might develop effectively adaptive immunity. Thus, the fully virulent Y. pestis strain as an origin to develop live efficacious vaccines might be an optimal choice.…”
Section: Developing Live Attenuated Vaccines Based On Fully Virulent mentioning
confidence: 99%
“…The study indicated that the seroprevalence to the F1 antigen in all recovered patients is 78.5%. In patients infected more than a decade, the antibody-positive rate still remains 69.5% [86]. The positive occurrence of the F1 antibody in patients was high, but approximately 30% of the recovered patients remained sero-negative to both F1 and LcrV antigens.…”
Section: Altering Immune Response To Specific Antigens Of Y Pestis Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Although clinical isolates of Y. pestis lacking F1 expression have been reported (39), expression of LcrV is an absolute requirement for virulence in plague (40,41). In addition, serum antibodies from patients fully recovered from naturally occurring bubonic plague were reported to predominantly recognize both F1 and LcrV antigens for up to 10 years postinfection (42). Therefore, both F1 and LcrV are considered key protective antigens for incorporation into a bivalent plague vaccine.…”
mentioning
confidence: 99%